Monitoring System of Oxygen and Carbondioxide in Controlled Atmosphere Storage System - Argo, Bambang Dwi; Lastriyanto, Anang; Astuti, Nuraini Puji (Fakultas Teknologi Pertanian Universitas Brawijaya, 2008)
One of the ways in pickling process of main food material of vegetables and fruits is storage. Principally, the control of metabolism during storage, such as respiration, transpiration, disease infection, is designed to lengthen shelf life of horticultural products. Â The purpose of storage of fruits and vegetables is to lengthen product utilization, to control market demand, and to increases benefits. So far, the system of controlled atmosphere storage is still done manually either by observation of gas composition or changing gas inside the packaging. Therefore, it is needed to modify equipment for monitoring system and controlling gas automatically, so the changes of gas volume and composition in storage space of CAS can be detected.Â Equipment applied in this research was microcontroller AT89S51 and its arrangement system by using computer. It had an existence of communication between a microcontroller system and a personal computer through IC RS 232. At this research the oxygen concentration changed from 21% to 2% and the carbon dioxide concentration increased from 0.03% to 2.5% at temperature of 26oC. This condition was suitable for apple var. Rome Beauty storage.Keywords: oxygen, carbon dioxide, CAS, MKAT89S51, personal computer